What Does the Public Prefer Versus What Is the Public Ready to Forgo?. Issue 4 (December 2021) - Kaplan, Giora; Connelly, Yaron
The present study uses a novel approach to assess the publics' ability to cope with priority setting and rationing in health care by asking what the public is willing to forego. Items for disinvestment were presented in three separated dimensions: Categories of medical care, quality of service, and items representing social values. A telephone survey was conducted among a representative sample of the Israeli public (N = 609). The response rate was 51%. We identify a few items that a high proportion of the population express readiness to forgo: a drug for smoking cessation, budgets for improving appearance and comfort in medical facilities, and a product for preventing surgical scars. Furthermore, over a quarter of the public was ready to forgo many other items. We found that less than 10% justified their selection in terms of "personally not important to me, " while most respondents evaluated the items they chose to forgo as "less effective or less essential in comparison to others." The study found that most respondents, when exposed to a range of health system components, were able to identify at least one item that they will be willing to forgo in a time of economic crisis.